2016
DOI: 10.1364/ao.56.000b97
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency, 154  W CW, diode-pumped Raman fiber laser with brightness enhancement

Abstract: We demonstrate a high-power, high-efficiency Raman fiber laser pumped directly by laser diode modules at 978 nm. 154 W of CW power were obtained at a wavelength of 1023 nm with an optical to optical efficiency of 65%. A commercial graded-index (GRIN) core fiber acts as the Raman fiber in a power oscillator configuration, which includes spectral selection to prevent generation of the second Stokes. In addition, brightness enhancement of the pump beam by a factor of 8.4 is attained due to the Raman gain distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 17 publications
0
30
0
1
Order By: Relevance
“…[5] with a focus on the opportunities of high-quality beam generation using fiber Bragg gratings (FBGs) as cavity mirrors [7][8][9][10] , whereas second one aims at high-power capabilities based on freespace pump coupling and bulk mirrors cavity [4,11,12] . In the last case, up to 154 W power is obtained at ∼1020 nm [12] , but Raman output at this wavelength is not as interesting, because higher power and narrower linewidth are available from YDFLs [13,14] . In addition, in spite of significant improvement of the output beam quality (M 2 = 4-8) in comparison with that for the pump beam (M 2 ∼ 20) due to the Raman clean-up effect in GRIN fibers, it is far from singlemode regime.…”
Section: S a Babinmentioning
confidence: 99%
“…[5] with a focus on the opportunities of high-quality beam generation using fiber Bragg gratings (FBGs) as cavity mirrors [7][8][9][10] , whereas second one aims at high-power capabilities based on freespace pump coupling and bulk mirrors cavity [4,11,12] . In the last case, up to 154 W power is obtained at ∼1020 nm [12] , but Raman output at this wavelength is not as interesting, because higher power and narrower linewidth are available from YDFLs [13,14] . In addition, in spite of significant improvement of the output beam quality (M 2 = 4-8) in comparison with that for the pump beam (M 2 ∼ 20) due to the Raman clean-up effect in GRIN fibers, it is far from singlemode regime.…”
Section: S a Babinmentioning
confidence: 99%
“…Yao et al proposed an LD-pumped RFL in 2015, obtaining a 20 W laser from GRIN fiber with an M 2 that was improved from 22 to 5, and a BE of 5.2 [27] . In 2016, Glick et al reported an LDpumped RFL based on GRIN fiber [28] , and the maximum power output reached 154 W with an M 2 of 8 and a BE of 3 through optimizing the fiber length [29] . Zlobina et al also studied RFL based on GRIN fiber, and the beam quality was quite good with an M 2 of~1.2 and a BE of~40, and the demonstrated power was 10 W [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Then higher power output is acquired through fiber lasers employing integrated Yb-Raman gain [12][13][14], nevertheless the brightness decreases in the Raman shifting process and the issues of PD reappear which will influence the performance of laser system. Recently the fast development of fiber components and the brightness enhancement of pump lasers make it possible for power scaling in passive fibers that employ pure Raman gain [15][16][17][18][19][20][21][22]. For instance, using graded-index (GRIN) fiber in core-pumped structure has a relatively simple construction and enhances the brightness in fiber core.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Y. Glick et al report an LD-pumped Raman fiber laser in free space configuration which obtain 80 W Raman laser output, and brightness enhancement is achieved through the beam clean-up procedure of GRIN fiber in the cavity [18]. Then by means of modifying the system and adding up pump energy the lasing power increases to 154 W [19]. In 2017, A. Zlobina et al propose an all-fiber Raman fiber laser that also utilizes GRIN fiber and acquire power of 50 W at 954 nm, while the FBGs inscribed in GRIN fiber are the key devices which are specially fabricated for efficient reflection and mode selection effect [20].…”
Section: Introductionmentioning
confidence: 99%